2015
DOI: 10.1002/anie.201503365
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Evolution Catalyzed by a Mononuclear Ruthenium Complex Bearing Pendant SO3 Groups

Abstract: Rational molecular design of catalytic systems capable of smooth O-O bond formation is critical to the development of efficient catalysts for water oxidation. A new ruthenium complex was developed, which bears pendant SO3(-) groups in the secondary coordination sphere: [Ru(terpy)(bpyms)(OH2)] (terpy=2,2':6',2''-terpyridine, bpyms=2,2'-bipyridine-5,5'-bis(methanesulfonate)). Water oxidation driven by a Ce(4+) oxidant is distinctly accelerated upon introduction of the pendant SO3(-) groups in comparisons to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…Recent study by Masaoka and co-workers revealed that the pendant SO 3 À groups on the catalyst could capture CANt o enhance its activity. [25] In our 2/CAN water oxidation system, however, the CAN concentration was so high that the assistance of pendant SO 3 À groups of complex 2 was negligible if there was any in the water oxidation system.…”
Section: Angewandte Chemiementioning
confidence: 73%
See 1 more Smart Citation
“…Recent study by Masaoka and co-workers revealed that the pendant SO 3 À groups on the catalyst could capture CANt o enhance its activity. [25] In our 2/CAN water oxidation system, however, the CAN concentration was so high that the assistance of pendant SO 3 À groups of complex 2 was negligible if there was any in the water oxidation system.…”
Section: Angewandte Chemiementioning
confidence: 73%
“…As shown in Figure 1, complex 1 displayed two peaks at 460 nm and 510 nm in acetonitrile solution, typical from MLCT [d(Ru)!p*(bipyridine) and p*(pyridine)] states. [25] In contrast to the fact, i.e., the energy of charge transfer bands increases with solvent polarity, [50] the aqueous solution of complex 1 showed weaker and bathochromic-shifted absorptions at 480 and 530 nm. This implied the aggregation behavior of amphiphilic complex 1 in water.…”
Section: Tomeetthesustainableproductionofcleanenergydemandsmentioning
confidence: 91%
“…The former half reaction is less energy demanding compared with the latter one, which is the key step and is always considered as a bottleneck because it requires the transfer of four electrons and formation of the O−O bond . Over the past decades, a great quantity of molecular catalysts in relation to mono‐, di‐, and polynuclear Ru‐, Ir‐, Mn‐, Co‐, Fe‐ and Cu‐based metal complexes have been developed. Among them, Ru‐based WOCs are the most representative.…”
Section: Methodsmentioning
confidence: 99%
“…The developmento fw ater oxidationc atalysts (WOCs) is an important step towards meeting our future energy demands. [1] In this respect, increasing numberso fh omogeneous [2,3] and heterogeneous [4] electrocatalysts based on preciousn oble metals have been reported as efficient WOCs in recent years. Among these, the homogeneous catalysts have advantages arising from the availability of rich mechanistic information from such systems, which is vital for the development of highly efficient catalysts.…”
Section: Introductionmentioning
confidence: 99%